Antibacterial and Anti-Diarrheal Potential of Andaliman (Zanthoxylum acanthopodium DC) Methanol and Nanoemulsion Extract - Chiuman , Linda; Singh, Wanti Natalia; Saragih, Delfia Rehuela; Rahyani, Oktavini Handayani Fikri; Rena Meutia (JST (Jurnal Sains dan Teknologi), 2024)
Diarrhoea is one of the prevalent global health problems, causing cases of death and morbidity in various age groups for people around the world. Andaliman is a typical herbal plant of North Sumatra with multiple benefits that have been studied previously. This study aims to analyze the antibacterial and anti-diarrheal potential of methanol extract and nanoemulsion of Andaliman (Zanthoxylum acanthopodium). This study used laboratory experimental research with a post-test-only group design. Antibacterial testing was carried out using the disc diffusion method with three repetitions of four extract concentrations. The standard group used ciprofloxacin 5μg, and the control group used DMSO. Then, we continued with the microdilution method with an initial concentration of 500mg/Dl extract to determine the minimum inhibitory and kill levels. An anti-diarrhoea study was conducted using 30 Wistar rats treated with nanoemulsion extract. The standard group was given loperamide 3 mg/KgBB, and the control group was given CMC Na 0.25 ml. Rats were induced with castor oil, and the frequency of defecation and liquid faeces were observed for 1 hour. Andaliman (Zanthoxylum acanthopodium) methanol extract showed a moderate inhibitory effect against E.Coli, with KHM and KBM of 55.56 mg/mL. Potential as anti-diarrhoea, Andaliman nano emulsion extract showed a significant difference at 50mg/KgBB dose for diarrhoea frequency and loose stools. However, no significant differences were found in gastrointestinal and entero-pooling results. Based on the results, it can be concluded that methanol extract and nanoemulsion of andaliman (Zanthoxylum acanthopodium) showed antibacterial activity against E.Coli and showed anti-diarrhea potential. The expected implication is that andaliman can be an alternative treatment for diarrhoea, especially for diarrhoea caused by Escherichia coli.